Veterinary-Sanitary Evaluation of the Effect of the Innoprovet Probiotic on Chicken Eggs - Ilyosovich, Ilyosov Zafar.; Rayimjonovna, Nasimova Dildora; qizi, Matmurodova Nafosat Baxtiyor; Sitora, Rajabova (American Journal of Biology and Natural Sciences, 2026)
The present study was conducted to evaluate the effect of the probiotic preparation “Innoprovet” on the productivity of laying hens and the veterinary-sanitary quality of eggs. The experiment was carried out at the “Qorasuv Parranda Fayz” poultry farm in Jomboy district, Samarkand region. A total of 60 Lohmann Sandy laying hens were divided into two groups: an experimental group (30 birds) and a control group (30 birds). The hens in the experimental group received the probiotic “Innoprovet” through drinking water at a dosage of 1 ml per 1 liter of water in addition to the standard farm ration, while the control group was maintained on the standard ration only. The study lasted for 120 days. During the experimental period, egg production rate, egg weight, shell quality, feather condition, feather pecking behavior, and egg pecking were monitored. Veterinary-sanitary and organoleptic examinations were performed on 168 eggs collected from both groups. The eggs were assessed according to their weight, shell characteristics, and general quality indicators and subsequently classified into commercial grades. The results demonstrated that the use of the probiotic had a positive effect on the productive performance of laying hens and contributed to improvements in several egg quality parameters. The findings indicate that “Innoprovet” can be recommended as an effective probiotic supplement for enhancing egg production and improving the veterinary-sanitary quality of eggs in poultry farming.